Treatment and Bleeding Complications of Cancer-Associated Venous Thromboembolism: A Korean Population-Based Study - Kim, Sang-A; Lee, Ju Hyun; Lee, Ji Yun; Hwang, Hun-Gyu; Kim, Yang-Ki; Yhim, Ho-Young; Hong, Junshik; Lee, Jeong-Ok; Bang, Soo-Mee (Thrombosis and Haemostasis, 2022)
Objectives This study investigated the treatment pattern and the rate of bleeding complications in real-world practice in cancer-associated venous thromboembolism (CT) patients.Methods We used the Korean Health Insurance Review and Assessment Service database (2014–2018). Among patients with venous thromboembolism, patients with concomitant malignancy diagnostic codes were categorized as CT, while all others were categorized as non-CT. Treatments were categorized as direct oral anticoagulant (DOAC), parenteral anticoagulant (PAC), warfarin, and mixed anticoagulants.Results We identified 27,205 CT and 57,711 non-CT patients. DOACs were the most frequently used anticoagulants. The proportion of patients treated with PAC was higher in CT than in non-CT patients (35.7 vs. 19.5%; p < 0.01). In CT, the cumulative incidence of any/major bleeding was higher with DOAC (8.1%/3.9%) than with PAC (7.5%/3.2%; p = 0.04 and 0.01, respectively). However, there was no difference in major bleeding when compared with warfarin (p = 0.11) or mixed anticoagulants (p = 0.94). Overall, gastrointestinal (GI) cancer patients showed higher risks of bleeding. The cumulative incidence of major GI bleeding was higher with DOAC than with PAC (4.9 vs. 3.0%; p < 0.01), while there was no difference compared with warfarin (p = 0.59) or mixed anticoagulants (p = 0.80). Major bleeding with each DOAC showed no difference among entire CT (p = 0.94), GI cancer (p = 0.27), and genitourinary cancer (p = 0.88) patients.Conclusion Five years after their introduction into clinical practice, DOACs have become the most prescribed anticoagulant in Korea. In our patient population, bleeding complications occurred more frequently in CT than in non-CT, especially in patients treated with DOACs.
Keywords: anticoagulants; hemorrhage; heparin; low-molecular-weight heparin; venous thromboembolism